Detection of minimal residual disease by polymerase chain reaction in b cell malignancies - Moos, Marion; Schulz, Renate; Cremer, Friedrich Walter; Sucker, Christoph; Schmohl, Dagmar; Döhner, Hartmut; Goldschmidt, Hartmut; Haas, Rainer; Hunstein, Werner (Stem cells, 1995)
It was the aim of this study to examine the prognostic value of the detection of minimal residual disease (MRD), with the help of the polymerase chain reaction (PCR), in patients with non-Hodgkin's lymphoma (NHL) and multiple myeloma (MM) who underwent sequential high-dose therapy with peripheral blood progenitor cell (PBPC) support, and in patients with acute myeloid leukemia (AML) of the subclass M4Eo who underwent high-dose consolidation therapy. Basis for the application of a PCR assay in these disease entities are the following specific gene rearrangements: the t(14;18) translocation in a high percentage of NHL, the clonal rearrangement of the Ig heavy chain locus resulting in a unique complementary determining region 3 (CDR3) for MM region and the inversion 16 characteristic for the M4Eo subclass of AML. Before the G-CSF-supported cytotoxic chemotherapy was given, 65% of the 52 patients with low- and intermediate-grade NHL enrolled into the study had PCR+ bone marrow (BM) and/or peripheral blood (PB) samples. The majority of patients (29 of 52) were autografted with a PCR+ transplant. The proportion of harvests containing t(14;18)+ cells was two-fold less in patients mobilized in first remission than in those with a history of previous treatment failure. This was also reflected when examining the B cell contents of the harvests measured as CD19+ cells with a 3.3-fold smaller proportion of CD19+ cells in leukapheresis (LP) products of patients mobilized in first remission. Patients who received a PCR- transplant are in remission and remained PCR- in BM and PB samples post-transplantation. Conversion to PCR-negativity in BM and PB samples post-transplantation was observed in 11 of 19 patients who were also in remission. In contrast, 6 of 29 patients who were autografted with PCR+ products relapsed, while 4 of them presented with PCR- samples on several occasions post-transplantation. In patients with MM, the assessment of MRD in PBPC harvests was based on the CDR3 regions of the Ig heavy chain locus as a marker for clonality. The great majority of LP products (17 out of 19) contained tumor cells. To prove positive enrichment procedures for the elimination of tumor cells, CD34+ and CD19+ cell fractions obtained from LP samples in an experimental setting via preparative flow cytometry were analyzed for MRD resulting in PCR-negativity for all CD34+ fractions. The results of the four patients with AML M4Eo and inversion 16 are preliminary, with a tendency of persistence of PCR-positivity after finishing the high-dose consolidation therapy. In one case, recurrence of disease was accompanied by an increase of the signal strength in the PCR assay. Longer follow-up periods are necessary to determine the prognostic value of these PCR findings in the different disease entities.
Gesehen am 05.11.2024